Lithium salt doped porous carbon coated graphite composite material for energy storage battery and preparation method of lithium salt doped porous carbon coated graphite composite material

By doping lithium salt in porous carbon and mixing it with carboxymethyl cellulose lithium, coating it on the graphite surface to form a composite material with a core-shell structure, the problems of different conductivity and reduced energy density of the cladding layer in the prior art are solved, and the fast charging performance of the material is improved and the energy density is taken into account.

CN119627075APending Publication Date: 2025-03-14广东宏璟新能源科技有限公司
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411789799.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The electronic conductivity of the existing fast-charging graphite negative electrode material has a limited improvement in its fast-charging performance, and the energy density of lithium salt doped materials is reduced. The porous carbon material is low for the first time and cannot be used directly as a negative electrode material.

Method used

Lithium salt is doped in porous carbon and mixed with lithium carboxymethyl cellulose to coat the graphite surface to form a core-shell structure of lithium salt doped in porous carbon coated graphite composite material.

Benefits of technology

It improves the liquid retention and ion transport performance of the cladding layer, improves the ratio and low temperature performance of graphite, while taking into account the first-time efficiency of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627075A_ABST
    Figure CN119627075A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium salt doped porous carbon coated graphite composite material for an energy storage battery and a preparation method thereof, the composite material has a core-shell structure, the core is graphite, and the shell is a lithium salt doped porous carbon complex. The preparation method comprises the following steps: uniformly mixing amino resin, a pore-forming agent and a heteroatom compound of the pore-forming agent, curing, activating to obtain porous carbon, adding the porous carbon into an inorganic lithium salt, uniformly mixing, and carrying out spray drying to obtain lithium salt doped porous carbon; the preparation method comprises the following steps: adding lithium salt doped porous carbon into a carboxymethyl cellulose lithium solution, uniformly dispersing, then adding into a graphite material, uniformly dispersing, spray-drying, and carbonizing to obtain the lithium salt doped porous carbon coated graphite composite material. According to the obtained material, the coating layer lithium salt is doped with porous carbon, so that the liquid absorption and retention capacity of the material is improved, the diffusion rate of lithium ions is increased, and the rate capability is improved; meanwhile, the expansion of the composite material in the charging and discharging process is reduced by utilizing the low expansion of the porous carbon, and the cycle performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion battery material preparation, in particular to a lithium salt-doped porous carbon-coated graphite composite material used in energy storage batteries and a preparation method thereof. Background Art

[0002] The fast-charging graphite negative electrode materials currently on the market mainly coat soft carbon or hard carbon on the surface of small-particle graphite to improve the fast-charging performance of the material, relying on the disordered layer structure of soft carbon or hard carbon to improve the diffusion rate of lithium ions, but the coating layer material has poor electronic conductivity, resulting in limited improvement in the fast-charging performance of the material. Although some researchers have increased the ion transfer rate of the material by doping lithium salts in the coating layer, the energy density is reduced because the lithium salt compound itself does not provide capacity. As one of the carbon-based materials, porous carbon, with its high specific surface area and porous structure, is beneficial to the material's liquid retention and ion transfer, but due to many defects, its initial efficiency is reduced and it cannot be used directly as a negative electrode material. It needs to be pre-lithiated to improve the initial efficiency of the material and coated on the graphite surface to improve fast charging and low-temperature performance. Summary of the invention

[0003] In order to improve the fast charging and low-temperature performance of graphite and take into account the initial efficiency of the material, the present invention innovatively proposes to dope lithium salt in porous carbon and mix it with lithium carboxymethyl cellulose and coat it on the graphite surface, thereby improving the liquid retention and ion transmission performance of the coating layer material, thereby improving the rate and low-temperature performance of graphite. At the same time, a preparation method of a lithium salt-doped porous carbon-coated graphite composite material used in energy storage batteries is provided.

[0004] A lithium salt-doped porous carbon-coated graphite composite material for energy storage batteries, characterized in that the composite material presents a core-shell structure, the core is graphite, and the shell is a lithium salt-doped porous carbon composite; calculated according to the mass ratio of the composite material, the mass ratio of the shell is 5-10wt%.

[0005] A method for preparing a lithium salt-doped porous carbon-coated graphite composite material for an energy storage battery, characterized in that it comprises the following steps:

[0006] Step S1:

[0007] According to the mass ratio of amino resin: pore-forming agent: heteroatom pyridine acid compound: inorganic lithium salt = 100: 1-5: 1-5: 5-15, the amino resin, pore-forming agent and heteroatom compound are mixed evenly, cured at 400-600° C. for 1-6 hours, then heated to 1000-1200° C., and activated with water vapor for 1-6 hours to obtain porous carbon; the obtained porous carbon material is added to 1-10wt% inorganic lithium salt, mixed evenly, and spray-dried to obtain lithium salt-doped porous carbon.

[0008] Step S2:

[0009] According to the mass ratio of porous carbon doped with lithium salt: lithium carboxymethyl cellulose: graphite material = 5-15: 1-5: 100, lithium carboxymethyl cellulose is added to deionized water to prepare a solution with a mass concentration of 1-10wt%, and then the lithium salt doped porous carbon and graphite material are added and dispersed evenly, spray dried (inlet temperature 200°C, outlet temperature 80°C, flow rate 0.1kg / h, 2h), and carbonized at 1000-1300 for 1-6h to obtain a lithium salt doped porous carbon coated graphite composite material.

[0010] In the step S1, the amino resin is one of butanol-modified urea-formaldehyde resin, polyurethane resin, polyamide resin, and methacrylated polyurethane resin.

[0011] In step S1, the pore-forming agent is one of polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone or paraffin.

[0012] The heteroatom pyridine acid compound in step S1 is one of 3-pyridinecarboxylic acid, 2,5-pyridinedicarboxylic acid, 1-pyridine acid, 3,5-pyridinedicarboxylic acid, pyridine-3-carboxylic acid or pyridine-4-carboxylic acid.

[0013] In the step S1, the inorganic lithium salt is one of lithium niobate, lithium cerate and lithium zirconate.

[0014] Beneficial effects:

[0015] 1. An amino resin is mixed with a pore-forming agent, a heteroatom pyridine acid compound, and an inorganic lithium salt, and carbonized to obtain a lithium-doped hard carbon material. Pores are formed by water vapor activation to obtain a lithium-doped porous carbon, which has the characteristics of good liquid retention and high lithium ion transfer rate. The amino resin is mixed with a carboxymethyl cellulose lithium binder and a lithium supplement agent, and carbonized to obtain a lithium supplement agent / porous carbon / amorphous carbon composite. The lithium supplement agent releases lithium ions during the charge and discharge process to compensate for the lithium ions consumed by the formation of the SE I film on the surface of the porous carbon, thereby improving the cycle performance. At the same time, the porous carbon has a high specific surface area and stores more lithium ions to increase the diffusion rate of lithium ions, while the amorphous carbon has good compatibility with the electrolyte, thereby improving the storage performance, processing performance, and cycle performance.

[0016] 2. The heteroatom pyridine acid compound of the present invention is different from other heteroatom compounds (such as ammonia, pyrrole, phosphoric acid, etc.). During the sintering process, the acid compound is dehydrated to form an -O- chemical bond to form a porous structure and realize nitrogen doping, thereby improving the electronic conductivity of the porous carbon. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a SEM image of the porous carbon-doped lithium salt-coated graphite composite material prepared in Example 1. DETAILED DESCRIPTION

[0018] Example 1

[0019] A method for preparing a lithium salt-doped porous carbon-coated graphite composite material for an energy storage battery comprises the following steps:

[0020] Step S1:

[0021] 100g of butanol-modified urea-formaldehyde resin, 3g of polyvinyl alcohol and 3g of 3-picolinic acid were mixed evenly, cured at 500°C for 3h, then heated to 1100°C, and activated with water vapor for 3h to obtain porous carbon; the obtained porous carbon material was added to 200g of 5wt% lithium niobate aqueous solution, mixed evenly, and spray-dried (inlet temperature 200°C, outlet temperature 80°C, flow rate 0.1kg / h, 2h) to obtain lithium salt-doped porous carbon.

[0022] Step S2:

[0023] 3g of lithium carboxymethyl cellulose was added to 60g of deionized water to prepare a solution with a mass concentration of 5wt%, and then 10g of lithium salt-doped porous carbon and 100g of artificial graphite material were added and dispersed evenly, spray dried (inlet temperature 200℃, outlet temperature 80℃, flow rate 0.1kg / h, 2h), and carbonized at 1200℃ for 3h to obtain a lithium salt-doped porous carbon-coated graphite composite material.

[0024] Example 2

[0025] A method for preparing a lithium salt-doped porous carbon-coated graphite composite material for an energy storage battery comprises the following steps:

[0026] Step S1:

[0027] 100g of polyurethane resin, 1g of polyvinyl butyral and 1g of 2,5-pyridinedicarboxylic acid were mixed evenly, cured at 400°C for 6h, then heated to 1000°C, and activated with water vapor for 6h to obtain porous carbon; the obtained porous carbon material was added to 150g of 1wt% lithium cerate solution, mixed evenly, and spray dried (inlet temperature 200°C, outlet temperature 80°C, flow rate 0.1kg / h, 2h) to obtain lithium salt-doped porous carbon.

[0028] Step S2:

[0029] 1g of lithium carboxymethyl cellulose was added to 100g of deionized water to prepare a solution with a mass concentration of 1wt%, and then 5g of lithium salt-doped porous carbon and 100g of artificial graphite material were added and dispersed evenly, spray dried (inlet temperature 200°C, outlet temperature 80°C, flow rate 0.1kg / h, 2h), and carbonized at 1000°C for 6h to obtain a lithium salt-doped porous carbon-coated graphite composite material.

[0030] Example 3

[0031] A method for preparing a lithium salt-doped porous carbon-coated graphite composite material for an energy storage battery comprises the following steps:

[0032] Step S1:

[0033] 100g of polyamide resin, 5g of polyvinyl pyrrolidone and 5g of 1-pyridine acid were mixed evenly, cured at 600°C for 1h, then heated to 1200°C, and activated with water vapor for 1h to obtain porous carbon; the obtained porous carbon material was added to 150g, 10wt% lithium zirconate, mixed evenly, and spray-dried (inlet temperature 200°C, outlet temperature 80°C, flow rate 0.1kg / h, 2h) to obtain lithium salt-doped porous carbon.

[0034] Step S2:

[0035] 5 g of lithium carboxymethyl cellulose was added to 50 g of deionized water to prepare a solution with a mass concentration of 10 wt%, and then 15 g of lithium salt-doped porous carbon and 100 g of artificial graphite material were added and dispersed evenly, spray dried (inlet temperature 200 ° C, outlet temperature 80 ° C, flow rate 0.1 kg / h, 2h), and carbonized at 1300 for 1h to obtain a lithium salt-doped porous carbon-coated graphite composite material.

[0036] Comparative Example 1:

[0037] The difference from Example 1 is that no lithium niobate aqueous solution is added, and the rest is the same as Example 1.

[0038] Comparative Example 2:

[0039] The difference from Example 1 is that the porous carbon-doped lithium salt is replaced by asphalt, and the rest is the same as Example 1.

[0040] 1. SEM test

[0041] The lithium salt-doped porous carbon-coated graphite composite material prepared in Example 1 was subjected to SEM testing, and the results are as follows: Figure 1 As shown in the figure, it can be seen that the graphite composite material prepared in Example 1 presents a single particle structure, has a small amount of microporous structure on the surface, and the particle size is between 10-15 μm.

[0042] 2. Physical and chemical properties and button battery test

[0043] The specific surface area, powder OI value, specific capacity and initial efficiency of the graphite composite materials prepared in Examples 1-3 and Comparative Examples 1-2 were tested. Test method: GBT-24533-2019 "Graphite negative electrode materials for lithium-ion batteries". At the same time, the OI value of the powder material was tested by XRD. The graphite composite materials obtained in Examples 1-3 and Comparative Examples 1-2 were assembled into button batteries A1, A2, A3, B1, and B2, respectively; the preparation method thereof is as follows: adding a binder, a conductive agent and a solvent to the negative electrode material, stirring and slurrying, coating on a copper foil, and drying and rolling. The binder used is LA132 binder, the conductive agent is SP, the negative electrode material is the graphite composite material prepared in Examples 1-3 and Comparative Examples 1-2, respectively, the solvent is double distilled water, and the ratio is: negative electrode material: SP: LA132: double distilled water = 94g: 2g: 4g: 220mL, and a negative electrode plate is prepared; the electrolyte is Li PF6 / EC+DEC (volume ratio 1:1, concentration 1.1mol / L), the metal lithium sheet is the counter electrode, the diaphragm is a polyethylene PE film, the simulated battery assembly is carried out in an argon-filled glove box, and the electrochemical performance is carried out on a Wuhan Blue Electric CT2001A battery tester, with a charge and discharge voltage range of 0.005V-2.0V and a charge and discharge rate of 0.1C. At the same time, the cycle performance of its button battery is tested (25°C, 0.1C / 0.1C, 100 weeks), and the diffusion coefficient of the powder materials of Examples 1-3 and Comparative Examples 1-2 is tested by GITT, and the test results are as shown in Table 1:

[0044] Table 1

[0045]

[0046] It can be seen from Table 1 that compared with Comparative Examples 1-2, the first discharge capacity, first efficiency, diffusion coefficient and powder OI ester of the graphite composite materials prepared in Examples 1-3 are significantly improved. The reason is that the lithium supplement agent is coated on the graphite surface to increase the diffusion rate of the material, reduce polarization, and improve the rate performance.

[0047] 3. Soft pack battery test:

[0048] The high initial efficiency fast charging graphite composite materials prepared in Examples 1-3 and Comparative Examples 1-2 were used as negative electrodes, lithium iron phosphate was used as the positive electrode material to prepare the positive electrode, LiPF6 (solvent is EC+DEC, volume ratio is 1:1, concentration is 1.3 mol / L) was used as the electrolyte, and celegard2400 was used as the separator to prepare a 2Ah soft-pack battery.

[0049] 3.1 Rate performance test

[0050] HPPC rate performance: 3C pulse charging, 4C pulse discharge, and test the charging DCR under different SOC conditions (10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%). The results are shown in Table 2:

[0051] Table 2

[0052]

[0053] As can be seen from Table 2, the HPPC (rate) performance of the soft-pack battery of the embodiment of the present invention is significantly better than that of the comparative example, that is, the charging time is shorter, indicating that the composite negative electrode material of the present invention has good fast charging performance. The reason may be that the embodiment material has a high diffusion coefficient and a large interlayer spacing, which increases the transmission rate of lithium ions and improves the rate performance.

[0054] 3.2 Cycle performance

[0055] The cycle test method is: 1C / 1C, 2.5-3.65V, 25±3℃, 500 weeks; the test results are shown in Table 2 below.

[0056] Table 3

[0057]

[0058] It can be seen from Table 3 that the liquid absorption and retention capabilities of the negative electrodes in Examples 1 to 3 are significantly better than those in the comparative examples. The reasons for this are as follows: the example materials have a high specific surface area, which improves the liquid absorption capacity of the materials and improves the cycle performance; at the same time, the example materials have a large interlayer spacing and a low full-charge expansion, which improves the cycle performance.

[0059] Although the preferred embodiments of the present invention have been described above in conjunction with the accompanying drawings, they are not intended to limit the scope of protection of the present invention. For those skilled in the art, the present invention may have various modifications and variations, and any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A lithium salt-doped porous carbon-coated graphite composite material for energy storage batteries, characterized in that: The composite material presents a core-shell structure, wherein the core is graphite and the shell is a lithium salt-doped porous carbon composite; calculated according to the mass ratio of the composite material, the mass ratio of the shell is 5-10wt%.

2. The method for preparing a lithium salt-doped porous carbon-coated graphite composite material for an energy storage battery according to claim 1, characterized in that: The steps include: Step S1: According to the mass ratio of amino resin: pore-forming agent: heteroatom pyridine acid compound: inorganic lithium salt = 100: 1-5: 1-5: 5-15, the amino resin, pore-forming agent and heteroatom compound are mixed evenly, cured at 400-600° C. for 1-6 hours, then heated to 1000-1200° C., and activated with water vapor for 1-6 hours to obtain porous carbon; the obtained porous carbon material is added to 1-10wt% inorganic lithium salt, mixed evenly, and spray-dried to obtain lithium salt-doped porous carbon. Step S2: According to the mass ratio of porous carbon doped with lithium salt: lithium carboxymethyl cellulose: graphite material = 5-15: 1-5: 100, lithium carboxymethyl cellulose is added to deionized water to prepare a solution with a mass concentration of 1-10wt%, and then the lithium salt doped porous carbon and graphite material are added and dispersed evenly, spray dried (inlet temperature 200°C, outlet temperature 80°C, flow rate 0.1kg / h, 2h), and carbonized at 1000-1300 for 1-6h to obtain a lithium salt doped porous carbon coated graphite composite material.

3. The method for preparing a lithium salt-doped porous carbon-coated graphite composite material for an energy storage battery according to claim 2, characterized in that: In the step S1, the amino resin is one of butanol-modified urea-formaldehyde resin, polyurethane resin, polyamide resin, and methacrylated polyurethane resin.

4. The method for preparing a lithium salt-doped porous carbon-coated graphite composite material for an energy storage battery according to claim 2, characterized in that: In step S1, the pore-forming agent is one of polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone or paraffin.

5. The method for preparing a lithium salt-doped porous carbon-coated graphite composite material for an energy storage battery according to claim 2, characterized in that: The heteroatom pyridine acid compound in step S1 is one of 3-pyridinecarboxylic acid, 2,5-pyridinedicarboxylic acid, 1-pyridine acid, 3,5-pyridinedicarboxylic acid, pyridine-3-carboxylic acid or pyridine-4-carboxylic acid.

6. The method for preparing a lithium salt-doped porous carbon-coated graphite composite material for an energy storage battery according to claim 2, characterized in that: In the step S1, the inorganic lithium salt is one of lithium niobate, lithium cerate and lithium zirconate.

Citation Information

Cited By

  • Preparation method of graphite composite material

    CN121672515A

  • A method for producing a graphite composite

    CN121672515B

  • Negative electrode material, preparation method thereof and battery

    CN122370372A